Pendekatan Supervisi Klinis Kepala Sekolah dalam Mengatasi Permasalahan Pembelajaran di SMP Muhammadiyah 4 Malang - Aril Deo Saputra; Shobihatul Fitroh Noviyanti; Aghitsna Naurah Al Jamilah; Olivia Nurry Qolby; Siti Nur Albaqiah (Al-Kindi, 2026)
This study aims to analyze the clinical supervision approach carried out by the principal in overcoming learning problems at SMP Muhammadiyah 4 Malang. The study used a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The data sources consisted of the principal and teachers as primary data sources, as well as school documents as secondary data sources. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study showed that clinical supervision was implemented through a collaborative and humanistic approach that emphasized communication, evaluation, guidance, and follow-up of the learning process. The learning problems found included the low reading ability of some students, differences in students’ learning abilities, the handling of students with special needs, and the less optimal classroom management and implementation of learning methods. As a follow-up to the supervision process, the school conducted additional classes, special assistance for students, routine teacher evaluations, and adjustments to learning strategies according to students’ needs. Clinical supervision had a positive impact on improving the quality of learning and increasing teachers’ awareness in improving the learning process, although its implementation still faced obstacles such as limited time and the lack of direct classroom observation